The viability of MCM-41 as separator in secondary alkaline cells - Meskon, Shahrul Razi; Othman, Raihan; Ani, Mohd Hanafi (Institute of Physics Publishing, 2018)
The viability of MCM-41 membrane as a separator material in secondary alkaline cell is investigated. The inorganic membrane was employed in an alkaline nickel-zinc system. MCM-41 mesoporous material consists of arrays of hexagonal nano-pore channels. The membrane was synthesized using sol-gel route from parent solution comprising of quarternary ammonium surfactant, cethyltrimethylammonium bromide C16H33(CH3)3NBr (CTAB), hydrochloric acid (HCl), deionized water (H2O), ethanol (C2H5OH), and tetraethylortosilicate (TEOS). Both the anodic zinc/zinc oxide and cathodic nickel hydroxide electrodeposited film were coated with MCM-41 membrane. The Ni/MCM-41/Zn alkaline cell was then subjected to 100-cycle durability test and the structural stability of MCM-41 separator throughout the progression of the charge-discharge cycles is studied. X-ray diffraction (XRD) analysis on the dismantled cell shows that MCM-41 began to transform to lamellar MCM-50 on the 5th cycle and transformed almost completely on the 25th cycle. The phase transformation of MCM-41 hexagonal structure into gel-like MCM-50 prevents the mesoporous cell separator from diminished in the caustic alkaline surround. This work has hence demonstrated MCM-41 membrane is viable to be employed in secondary alkaline cells.